Can Rehabilitative Travel Mobility improve the Quality of Life of Seasonal Affective Disorder Tourists? - Sha, Sha; Shen, Wencan; Yang, Zhenzhi; Dong, Liangquan; Li, Tingting (Frontiers in Psychology, 2022)
Rehabilitation mobility has become a new demand and travel mode for people to pursue active health. A large number of tourists choose to escape the cold in warm places to improve their health every winter. In this study, we collected the health index data of Seasonal Affective Disorder (SAD) tourists from western China before and after their cold escape in Hainan Island in winter, aiming to compare whether rehabilitating cold escape can improve the Quality of Life (QOL) of SAD tourists by hierarchical analysis. Compared with previous studies, this paper has the following contributions: Firstly, the study samples were accurately screened according to the pathogenesis of SAD tourists and the confounding factors were strictly controlled; Secondly, the observational experimental method was used to conduct inter-group and intra-group control studies on 695 samples, and the results were more objective and reliable. Thirdly, the effect of treatment on the quality of life (QOL) of 397 tourists in the rehabilitation mobility group was quantitatively evaluated from three factors including age, gender and sunshine exposure level by multivariate analysis of variance. Research results show that the rehabilitation environment brought by rehabilitation activities can help improve the health status of tourists. Therefore, this paper proposes the concept of "Tourism Therapy" and constructs a theoretical framework. The conclusion of this paper provides a scientific basis and reference for the study of tourism healing as a non-medical alternative therapy.